PERUMUSAN STRATEGI BISNIS UNTUK PENINGKATAN MARKET SHARE PT TERMINAL TELUK LAMONG - Bibin Retmawan (UNUSA Press, 2020)
The existence of a port really determines progress in an area, this is related to its function in the supply chain management distribution or logistic distribution system as a link between sea and land transportation modes to meet the needs of the community and industry which will ultimately affect economic growth in an area. Meeting the needs of the community will be fulfilled optimally, efficiently and effectively if the port as a logistical support system for the distribution of goods and people can run smoothly and well integrated. The purpose of this study is to analyze the right strategy at PT Terminal Teluk Lamong in winning the competition seen from the analysis of the internal environment and the analysis of the external environment. This research uses a qualitative approach with a case study approach. The sample of this research is key informants using purposive sampling and conducting interviews. The results of this study are that the Terminal PT Teluk Lamong is in a